Ethnomedicinal plants used in the treatment of skin diseases in Hyderabad Karnataka region, Karnataka, India - Policepatel, Shivakumar Singh (Asian Pacific Tropical Medicine Press, 2013)
OBJECTIVE: To document traditional medicinal plants knowledge used in treating skin diseases at Hyderabad Karnataka Region. METHODS: The information on the use of medicinal plants in the treatment of skin diseases was gathered from traditional herbal healers and other villagers through interviews. RESULTS: A total of 60 plants species belonging to 57 genera and 34 families were found useful and herewith described them along with the method of drug preparation, mode of administration, probable dosage and duration of treatment. Several new findings on the traditional rural practices were reported. CONCLUSIONS: The present study revealed that the Hyderabad Karnataka rural people is primarily dependent on medicinal plants for treating skin diseases.